First-principles study on the electronic structures and optical properties of Cs2XInCl6 (X= Ag, Na). (1st September 2022) - Luo, Muxuan; Zhao, Yongchao; Yang, Anqi; Chen, Qinfen; Zhang, Xiwu; Luo, Jiaolian
Abstract: The excellent properties and diversity of structural composition of environmentally benign and stable double perovskite materials have piqued the curiosity of a wide range of researchers. In the field of optoelectronic materials, all-inorganic halide double perovskite has emerged as a viable alternative to lead-based perovskite in recent years. The energy band structure, density of states, and optical properties of the all-inorganic halide double perovskite Cs2 XInCl6 (X = Ag, Na) were calculated and compared in this paper using the Castep code of Materials Studio software based on the density generalized function theory first principle plane wave pseudopotential method (DFT). The analysis of the results shows that Cs2 XInCl6 (X = Ag, Na) is a material with a wide direct band gap and exhibits good light absorption in the visible and ultraviolet regions. Cs2 AgInCl6 has better optical properties than Cs2 NaInCl6 due to differences in reflection spectra, absorption spectra, and energy loss, although the differences are not considerable, and the compound Cs2 XInCl6 (X = Ag, Na) has prospective applications in the field of optoelectronics. The computational results of this work contribute to a better understanding of the electronic and optical properties of Cs2 XInCl6 (X = Ag, Na), as well as their similarities and differences, and provide some ideas for the design of corresponding innovative experiments to seek more valuable discoveries in the field of optoelectronic and optical applications. Highlights: The present progress and trends in perovskite are briefly summarized. The similarities and differences between Cs2 AgInCl6 and Cs2 NaInCl6 were studied. Band gaps were computed using different functionals and compared to existing data. Both Cs2 AgInCl6 and Cs2 NaInCl6 have similar optical properties. It serves as a theoretical reference for later investigations.